Guide to construction and use of 6.30 mm (0.25 in) magnetic tape cartridge using GCR for data interchange, recording at 394 ftpmm(10 000 ftpi), 39 cpmm (1 000 cpi). Streaming mode Part 2, (30th June 1989) - British Standards Institution,
No abstract available